De feminino a feminista: transformação na escrita literária dos romances de Heloneida Studart - Souza, Ioneide Maria Piffano Brion de (2014)
This thesis intents to recover the incorporation of the issue of gender in the intellectual trajectory of Heloneida Studart through her fictional literature, having as objective the way that the issue of gender was thematized in the novels of the writer during the years from 1952 to 1978. It was aimed to examine how Heloneida inserted herself in the debates about women and gender relations in the period. My concerns were less a search to see if literate produces or reproduces stereotypical images of relations between women and men and more to understand the features that Heloneida made use and the main senses that wew used to construct such image well ajusted to the debates and categories that shaped her literary project, which was developing from both her subjective experiences, and from contacts that were made, namely: the house of Juvenal Galeno, the Communist Party, the feminist movement and the Brazilian Women Center. From this connection, subjective experiences and social places, theoretical formulations were born not only for her novels but also for her subsequent practical politics in favor of women.